Kebijakan Reorganisasi Perizinan Untuk Meningkatkan Kualitas Pelayanan Publik di Kota Yogyakarta - ISNAINI MUALLIDIN (Jurnal Studi Pemerintahan, 2011)
The purpose of this research was to evaluate the reorganization of the licensing policy to improve thequality of public services in the City Yoyakarta. The method used in this study was to evaluate theresearch methods of interviews, observation, and secondary data from relevant sources. The resultsshowed that the reorganization UPTSA into Dinas Perizinan has provided many benefits to society,because a permit can be done one door with an integrated system. So that a permits be efficient andeffective because of the simplification of systems and procedures for information technology-basedservices. The conclusion of this study was the reorganization of licensing policy has provided aparadigm shift in the public service-oriented accountability system that has been adjusted to the needsof the community.